Microfabrication Technologies for Oral Drug Delivery - Sant, Shilpa (2011)
Micro-/nanoscale technologies such as lithographic techniques and microfluidics offer promising avenues to revolutionalize the fields of tissue engineering, drug discovery, diagnostics and personalized medicine. Microfabrication techniques are being explored for drug delivery applications due to their ability to combine several features such as precise shape and size into a single drug delivery vehicle. They also offer to create unique asymmetrical features incorporated into single or multiple reservoir systems maximizing contact area with the intestinal lining. Combined with intelligent materials, such microfabricated platforms can be designed to be bioadhesive and stimuli-responsive. Apart from drug delivery devices, microfabrication technologies offer exciting opportunities to create biomimetic gastrointestinal tract models incorporating physiological cell types, flow patterns and brush-border like structures. Here we review the recent developments in this field with a focus on the applications of microfabrication in the development of oral drug delivery devices and biomimetic gastrointestinal tract models that can be used to evaluate the drug delivery efficacy.